2022
DOI: 10.7759/cureus.22363
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Bacterial Infection Rates Among Patients With COVID-19

Abstract: The aim of this study was to determine the factors and rates of secondary bacterial infections developed in patients after the diagnosis of COVID-19 and antimicrobial susceptibility to guide the empirical treatment and contribute to epidemiological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 20 publications
2
35
0
2
Order By: Relevance
“…In the present study, bloodstream infections were confirmed as the second most frequent infective complication, with a significant proportion being Gram-negative pathogens [ 21 , 53 , 54 ]. The elevated prevalence of Enterococcus spp.…”
Section: Discussionmentioning
confidence: 80%
“…In the present study, bloodstream infections were confirmed as the second most frequent infective complication, with a significant proportion being Gram-negative pathogens [ 21 , 53 , 54 ]. The elevated prevalence of Enterococcus spp.…”
Section: Discussionmentioning
confidence: 80%
“…In another recent report, the rate of bacterial co-infections was confirmed in 1055 COVID-19 patients via polymerase chain reaction (PCR) tests, demonstrating that K. pneumoniae was among the other detected bacteria [ 50 ].…”
Section: Collected Data and Discussionmentioning
confidence: 99%
“…Based on the findings of microbial culture tests, 92 (8.7%) patients had respiratory or circulatory tract infections that were microbiologically confirmed. Out of 61 patients, respiratory tract infections were found in 44 patients to be monomicrobial and 17 patients to be polymicrobial [ 42 ]. Of 94 included patients, 68% acquired at least one of the studied SBIs during their ICU stay.…”
Section: Higher Rates Of Sbis In Covid-19 Patients: a Primary Concernmentioning
confidence: 99%